2015
DOI: 10.14334/wartazoa.v24i4.1090
|View full text |Cite
|
Sign up to set email alerts
|

Developing Beef Cattle Industry at Smallholders to Support Beef Self-Sufficiency

Abstract: ABSTRAKLebih dari 90% pasokan daging sapi lokal berasal dari peternakan rakyat yang kurang efisien, sehingga pertumbuhan produksi daging sapi lokal belum dapat memenuhi permintaan nasional. Harga daging sapi impor lebih rendah dibandingkan daging lokal, sehingga di tingkat peternak terjadi penyesuaian harga yang merugikan. Naskah ini mendiskripsikan gagasan yang dapat memformulasikan strategi alternatif untuk membangun industri peternakan sapi potong rakyat. Strategi yang diperlukan untuk membangun industri pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
1
11
0
2
Order By: Relevance
“…As in other areas in Indonesia, in these study areas, cattle are kept in mixed farming systems and serve many objectives such as saving, producing manure, draught power and social and status (Widiati, 2006;Widiati, 2014). Livestock as a living bank, be indicated that farmers would sell their animals at any time to meet their special needs such as school fees, repair homes, and social needs of the community, so the livestock sold has not yet reached the maximum age for profit (Widiati, 2014).…”
Section: Production Systems Of Beef Cattle Farmingmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other areas in Indonesia, in these study areas, cattle are kept in mixed farming systems and serve many objectives such as saving, producing manure, draught power and social and status (Widiati, 2006;Widiati, 2014). Livestock as a living bank, be indicated that farmers would sell their animals at any time to meet their special needs such as school fees, repair homes, and social needs of the community, so the livestock sold has not yet reached the maximum age for profit (Widiati, 2014).…”
Section: Production Systems Of Beef Cattle Farmingmentioning
confidence: 99%
“…Livestock as a living bank, be indicated that farmers would sell their animals at any time to meet their special needs such as school fees, repair homes, and social needs of the community, so the livestock sold has not yet reached the maximum age for profit (Widiati, 2014). Breeders have a narrow agricultural land was about 1000 m 2 of flat land so that on the season of tilling, then the cattle used to pull plows.…”
Section: Production Systems Of Beef Cattle Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…The land used for grazing beef cattle has received permission from the local government, private sector, village and land owners. Beef cattle in Sukabumi Regency contributes to fulfill the demands as well as additional income for the farmers in the Sukabumi Regency and Sukabumi Regency area (Widiati, 2014;BPP Sukabumi Regency, 2019). Therefore, the Sukabumi Regency is considered feasible as as center of beef cattle business due to the potency of its natural and human resources.…”
Section: Introductionmentioning
confidence: 99%
“…However, beef consumption per capita per year of Indonesian people in 2015 was the lowest which was less than 2 kg, compared with China (3.8 kg), Malaysia (4.3 kg), Philippines (3 kg), Thailand (2 kg), and Vietnam (9.8 kg) [Department of Food and Agriculture, 2016]. In addition, in the last five years, imported beef was still accounted of more than 30% [Widiati, 2014]. This was because 95% of cattle in Indonesia were kept by rural people as an integrated farming system that have many constraints [CBS, 2013].…”
Section: Introductionmentioning
confidence: 99%